الاقتصاد الإسلامي إلى ما وراء الوضعية والمعيارية - عبد الرزاق بلعباس (International Institute of Islamic Thought, 2012)
يتناول هذا البحث استخدام البُعدين: المعياري والوضعي في الخطاب الاقتصادي الإسلامي، استنادًا إلى عينة شملت اثني عشر باحثًا، عبر الطريقة الإدراكية: إلى أي شيء يصلح؟ وقد خلصت إلى أن استخدام ثنائية "وضعي/ معياري" في الاقتصاد الإسلامي ما زال يفترض وجود حد فاصل بين ما يسمى بالوضعي وما يسمى بالمعياري، وهو وَهْم لا يوجد إلا في أذهان مَن يتحدثون عنه. وعليه، فمن الضرورة تجاوز هذه الثنائية وحصر استخدامها في الدراسات المقارنة، أو عند عرض الاقتصاد الإسلامي لغير المقتنعين به، أو الذين تعتريهم شبهات حوله. This paper addresses the use of the normative and positive prepositions in the Islamic economic discourse, based on responses of a sample of twelve researchers, using the cognitive method: What is used for? It concluded that the use of the dichotomy "positive vs. normative" in Islamic economics still assumes the existence of a clear-cut boundary between what it is called 'positive' and 'normative'. The paper considers such a preposition as an illusion that exists only in the minds of those who talk about it. In this regard, it is necessary to go beyond this dichotomy and restrict its use to comparative studies, or when it comes to present Islamic economics to those who are not convinced of it, or those who have suspicions of it.